2019
DOI: 10.1016/j.nicl.2019.101660
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic diaschisis following perinatal stroke is associated with clinical disability

Abstract: BackgroundPerinatal stroke causes most hemiparetic cerebral palsy and leads to lifelong disability. Understanding developmental neuroplasticity following early stroke is increasingly translated into novel therapies. Diaschisis refers to alterations brain structures remote from, but connected to, stroke lesions. Ipsilesional thalamic diaschisis has been described following adult stroke but has not been investigated in perinatal stroke. We hypothesized that thalamic diaschisis occurs in perinatal stroke and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 39 publications
5
35
1
Order By: Relevance
“…The importance of the thalamus in predicting hand motor function has been already discussed many times 63,64 . These results indicate that the thalamus connections with other motor regions are directly linked to the motor score as it was demonstrated recently by 65 …”
Section: Discussionsupporting
confidence: 63%
“…The importance of the thalamus in predicting hand motor function has been already discussed many times 63,64 . These results indicate that the thalamus connections with other motor regions are directly linked to the motor score as it was demonstrated recently by 65 …”
Section: Discussionsupporting
confidence: 63%
“…The importance of the thalamus in predicting hand motor function has been already discussed many times 47,48 . These results indicate that the thalamus connections with other motor regions is directly linked to motor score as it was demonstrated recently by 49 .…”
Section: Discussionsupporting
confidence: 86%
“…These different patterns may be due to the relatively larger lesion size in AIS encompassing both subcortical and cortical areas compared to PVI in which injury is more constrained to the periventricular white matter. It is interesting to note that while basal ganglia structures are typically remote from PVI damage, there were still detectible differences in connectivity between these areas compared to peers perhaps mediating motor dysfunction via diaschisis, a process previously investigated in perinatal stroke patients ( Finger et al, 2004 , Kirton et al, 2016b , Craig et al, 2019a , Craig et al, 2019b , Srivastava et al, 2019 ). Also of note is the finding that values for some features found to be predictive of motor function in the regression analyses were not different from peers.…”
Section: Discussionmentioning
confidence: 96%
“…The thalamus is also a central hub for integrating sensory inputs shunting information to specialized cortical areas for further processing via significant projections to the basal ganglia and cortex via cortico-basal ganglia-thalamo-cortical loops ( Lanciego et al, 2012 ). We have recently demonstrated that thalamic diaschisis is common in perinatal stroke ( Srivastava et al, 2019 ) and that altered thalamic volumes, particularly in the non-lesioned hemisphere, are associated with motor function ( Craig et al, 2019a ). Our findings here appear consistent with this previous evidence supporting an important role for the basal ganglia and thalamus in the developmental plasticity that determines motor function after perinatal stroke.…”
Section: Discussionmentioning
confidence: 99%